Over a million students use our free study notes to help them with their homework
Rcos(x + a) = Rcosxcosa - RsinxsinaBy comparing cosx - 3sinx to the new expression, we can see that:Rsina = 3 and Rcosa = 1If we square both and add them, we can see R = √(12Answered by Odin G. • Maths tutor8195 Views
A) y=ln(x) Ey = x Ey(dy/dx ) = 1 Eln(x)(dy/dx) = 1 X(dy/dx) = 1 Dy/dx = 1/xb) y = 1 * ln(x) V = ln(x) U= x dv/dx =1/x Du/dx = 1xln(x) - (integral) x * (1/x)xln(x) - (integ...
a) The surface area of a 3 dimensional shape is the sum total of the area of each side of the shape. This cuboid is 3x4x2, and so it has 2 sides with area 3x4 = 12, 2 sides with area 4x2 = 8, and 2 sides ...
Factorise fully the following expression: 2a2b + 6ab2 First, find the common terms by treating, 2a2b and 6ab2 as separate objects.We see common term...
←
667
668
669
670
671
→
Internet Safety
Payment Security
Cyber
Essentials